Growth and survival of larvae of the northern anchovy Engraulis mordax (Pisces: Engraulidae) reared under starvation conditions - Rodríguez-Murillo, J. A. (1989)
A batch of 2800 larvae of the northern anchovy, Engraulis mordax Girard, was maintained up to twelve days after hatching in the laboratory under supposed starvation conditions (20-300 orgs./1) and variable concentrations of the nanoflagellate Tetraselmis sp. (5,000-10,000 cells/ml). In contrast with previous reports, growth and survival under these conditions were comparable to those observed under optimum feeding conditions. This suggests strategies that may be used by marine fish larvae to avoid starvation and be able to grow in an environment characterized by low food densities. We question the existence of a "critical period". The ecological importance of nanoflagellates as a source of food in the marine environment is also suggested.